Women and religion in England 1500-1720 - Crawford, Patricia M. (London, UK Routledge, 1993)
Includes bibliographical references and index.
Keywords: Women in Christianity -- England -- history; England -- church history -- modern period, 1485- .; Women -- England -- Religious life -- history